Societal ethics and legal system facing contemporary marketing strategies: An Australian insight - Saee, John (Journal of Business Economics and Management, 2005)
An integral function of Australian market economy is the process of matching products/services with customers’ needs, desires and preferences. This process is greatly facilitated by advertising. Advertising not only provides information for the consumers but may also be used by the advertiser to bring subconscious consumer preferences or inchoate desires to the surface and to stimulate the demand for consumption. In carrying out these tasks, the advertiser must decide the pitch of the advertisement, the appropriate media to be used, the budget, the degree of exposure of the advertisement, market segmentation and claims to be made for the product (Goldring et al, 1987). Australian firms, irrespective of their size, rely heavily on advertising to market their products and services. The degree to which firms see the crucial role of advertising in their overall marketing mix, is clearly reflected in their annual allocation of advertising expenditure. “In 1997, total Australian advertising expenditures were $ 7.5 billion on advertising” (Miller and Layton, 2000, p. 590) All creative and imaginative forms of enticements and inducements being considered in the development of advertising strategies by these firms in an attempt to evoke favourable consumers’ responses for their offerings. Over time, some firms have come under increasing criticism by some sections of the community for their inappropriate promotional strategies which are seen as out of step with general community values and standards. Further in some instances, it is alleged that these firms have not only miscarried their social responsibility, but they have also breached the law covering Trade Practices operative in Australia and New Zealand. Such misguided corporate behaviour has also sparked negative consumerism concern, which if no corrective measure is adopted, will strategically harm the firm profit and viability. This research paper attempts to explore in some detail, aspects of advertising strategies within contemporary management paradigm. The paper will also shed light on corporate ethics /social responsibility. Finally, this paper will address legal obligations and consumerism concerns surrounding firms operating within the Australian society.First published online: 14 Oct 2010